2022
DOI: 10.1186/s13550-022-00912-z
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary mechanistic insights of a brain-penetrant microtubule imaging PET ligand in a tau-knockout mouse model

Abstract: Background Microtubules (MTs) are critical for cell structure, function, and survival. MT instability may contribute to Alzheimer’s disease (AD) pathogenesis as evidenced by persistent negative regulation (phosphorylation) of the neuronal microtubule-associated protein tau. Hyperphosphorylated tau, not bound to MTs, forms intraneuronal pathology that correlates with dementia and can be tracked using positron emission tomography (PET) imaging. The contribution of MT instability in AD remains unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Our prior mechanistic studies in tau knockout mouse models showed that [ 11 C]­MPC-6827 is more selective for destabilized MTs, and this preliminary investigation in four vervets with different CSF Aβ values also supports this interpretation. High-radiotracer uptake was observed in regions commonly associated with high tau and amyloid plaque densities. , Current preliminary results encourage the study PET imaging of the [ 11 C]­MPC-6827 radiotracer in more subjects of the AD model of NHPs to validate the results statistically and to establish the MT destabilization model for the AD pathogenesis.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Our prior mechanistic studies in tau knockout mouse models showed that [ 11 C]­MPC-6827 is more selective for destabilized MTs, and this preliminary investigation in four vervets with different CSF Aβ values also supports this interpretation. High-radiotracer uptake was observed in regions commonly associated with high tau and amyloid plaque densities. , Current preliminary results encourage the study PET imaging of the [ 11 C]­MPC-6827 radiotracer in more subjects of the AD model of NHPs to validate the results statistically and to establish the MT destabilization model for the AD pathogenesis.…”
Section: Resultssupporting
confidence: 65%
“…Our prior mechanistic studies in tau knockout mouse models 51 showed that [ 11 C]MPC-6827 is more selective for destabilized MTs, and this preliminary investigation in four…”
Section: Resultsmentioning
confidence: 76%
“…Additionally, our new in vitro, in vivo and ex vivo mechanistic studies showed that [ 11 C]MPC-6827 uptake is higher to destabilized MTs than stabilized MTs and that the uptake increases with brain Aβ/tau burden [31]. Postmortem studies on patients with confirmed AD showed higher radiopharmaceutical uptake than the cognitively normal age-matched controls [31]. Given the extensive work published from our group on [ 11 C]MPC-6827, the next steps would be to quantify its binding and metabolic characteristics in target (brain) and plasma-these data will strengthen its potential as a CNS PET radiopharmaceutical.…”
Section: Introductionmentioning
confidence: 87%
“…To study MT destabilization and its progression in all dementia disorders including AD, we developed the first brain-penetrating PET radiopharmaceutical, [ 11 C]MPC-6827 [27], and evaluated its imaging efficacy in rodents and nonhuman primate models of AD [27][28][29][30]. Additionally, our new in vitro, in vivo and ex vivo mechanistic studies showed that [ 11 C]MPC-6827 uptake is higher to destabilized MTs than stabilized MTs and that the uptake increases with brain Aβ/tau burden [31]. Postmortem studies on patients with confirmed AD showed higher radiopharmaceutical uptake than the cognitively normal age-matched controls [31].…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate that our synthesized [ 18 F]KSS3 can be used as in vivo PET imaging agent, we performed small animal microPET imaging using TriFoil microPET/CT system. 50 Male C57BL/J mice (n = 4, 22 ± 3 g) were anesthetized in an induction chamber with 2−3% isoflurane in oxygen, and a catheter was placed in the lateral tail vein. Each mouse was secured to a custom-designed acrylic bed equipped with a nosecone for gas anesthesia.…”
Section: N-(4-(2-fluoroethyl)phenyl)-6-(4-(3-isopropyl-124-oxadiazol-...mentioning
confidence: 99%